A Multicenter Collaboration for Simulation-Based Assessment of ACGME Milestones in Emergency Medicine. Issue 5 (October 2018) - Salzman, David H.; Watts, Hannah; Williamson, Kelly; Sergel, Michelle; Dobiesz, Valerie; DeGarmo, Noah; Vora, Samreen; Sharp, Louis J.; Wang, Ernest E.; Gisondi, Michael A.
Abstract : Summary Statement: In 2014, the six allopathic emergency medicine (EM) residency programs in Chicago established an annual, citywide, simulation-based assessment of all postgraduate year 2 EM residents. The cases and corresponding assessment tools were designed by the simulation directors from each of the participating sites. All assessment tools include critical actions that map directly to numerous EM milestones in 11 different subcompetencies. The 2-hour assessments provide opportunities for residents to lead resuscitations of critically ill patients and demonstrate procedural skills, using mannequins and task trainers respectively. More than 80 residents participate annually and their assessment experiences are essentially identical across testing sites. The assessments are completed electronically and comparative performance data are immediately available to program directors.